Mynaric Targets US Expansion to Take Laser Terminals into Widespread Use (Satellite Today, 2020)
Ghatore explained that beyond high throughput, laser communications are more secure than RF signals because they are not subject to jamming, making lasers an attractive option for government users, and applications like banking and enterprise that require high data security. [...]lasers don't require regulation of the International Telecommunications Union (ITU) or the FCC because light isn’t a regulated band. Because LEO satellites are closer together than satellites in Geostationary Orbit (GEO), lasers allow data to be transmitted between satellites in the same plane, lessening the burden on ground infrastructure. For the contract, Mynaric will supply multiple units of its flagship CONDOR terminals for Telesat’s work on the Blackjack Track B program, which looks to leverage commercial LEO technology for a global high-speed network for the U.S. Department of Defense (DoD).